Speckled lentiginous nevus with intranevic vitiligo depigmentation. - Patil, S.; Mitra, D. (European Journal of Pediatric Dermatology, 2024)
Vitiligo developing within congenital melanocytic nevi is a rare phenomenon. A case of a 13-year-old boy with new-onset vitiliginous lesions within a preexisting congenital segmental speckled lentiginous nevus is presented. This case highlights the importance of recognizing this unusual association and understanding its underlying pathogenesis. Based on clinical and histopathological data, possible mechanisms of this phenomenon are discussed and the relevant literature is reviewed.